Effect of Reverse Bias on Dye-Sensitized Technology: Lessons for Application in PV-Integrated Textile Fabric Designs Useable in Wajir, Vihiga, Kitui and Kajiado Counties in Kenya - Otakwa, Raphael Venson Makokha; Othieno, Herick; Oduor, Andrew Odhiambo (Journal of Technology Innovations in Renewable Energy, 2018)
This paper reports on the effect of reverse bias (RB) on dye-sensitized solar cells (DSSCs) that were investigated outdoor in Wajir (1o44’50’’ North, 40o 4’ 8’’ East), Vihiga (35o0’ East, 0o15’ North), Kitui (3o 0’ South, 37o 50’ East) and Kajiado (360o 5’ East, 30o 0’ South) in Kenya. The DSSCs’ J-V characteristics, namely, Voc, Jsc, FF and ?, were studied under varied RB potentials. This was achieved through partial, as well as complete shading of the DSSCs during their operation in the study sites, using a thick piece of black cloth, and measuring the obtaining J-V characteristics. Findings of the study reveal that subjecting the DSSC module that was investigated in Wajir to RB of between 1V and 4V triggered between 25.53% and 23.53% drop in the module’s efficiency (?), followed by its total breakdown thereafter. The modules studied in Vihiga, Kitui and Kajiado exhibited a similar trend, but with variations in ? under the different RB regimes. The DSSCs’ breakdown under RB regimes of over half their voltage ratings could be attributed to the damaging of their dye constituents. These findings are important for context-informed DSSC dye choices, as well as DSSC-integrated designs that appeal to local cultural textile fabrics, like shawls, kanzu (long robes) and light coats that women and men dress in, respectively, in Wajir, and blankets that both men and women wrap around their shoulders in Kajiado, as well as in local architectures. The findings underscore the existence of vast prospects for localized industries that innovate in DSSC-integrated designs for local espousal. They could form foundations for programs that mentor people, especially children and youths at local levels to engage in climate change-mitigating enterprises.